(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
The aim of the current study is to evaluate the effect of ultrasonic activation of two sealers: EndoSequenceBC and AH Plus on the fracture resistance of obturated roots.Materials and Method: Forty eight mandibular first premolars were decoronated to a length of 13 mmfrom the apex. The roots were divided into two groups (24 samples) to be obturated with gutta percha usingeither EndoSequence BC(Group I) or AH Plus (Group II) sealers. Each group was further subdivided intotwo subgroups (n=12). Subgroups IA and IIA were obturated without ultrasonic activation of the sealers.Subgroups IB and IIB were obturated with ultrasonic activation of the sealers. The activation of the sealerswas performed using size 15 ultrasonic K-file for a total of 20 seconds 2 mm short of the working length. Thesamples were subjected to fracture resistance test using a universal testing machine at a across head spead of0.5 mm/min. The data were analyzed using One way ANOVA and Tukey tests at a significant level of 0.05.Results: The fracture resistance mean values of the EndoSequence BC subgroups with and without activationwere significantly higher than those of AH Plus sealer (P<0.05).Conclusion: The ultrasonic activation of both sealers did not enhance the fracture resistance of obturatedroots.